Decreased basal thermogenesis is associated with the downregulation of cellular metabolic activity of organs and serum thyroid hormones in fasting Eurasian Tree Sparrows (Passer montanus) - Hong Jin; Qi Xia; Ziqing Gao; Yujie XuanYuan; Beibei Dong; Ming Li; Qingjian Liang; Jinsong Liu (Avian Research)
Food is a critical environmental factor that influences animal survival, especially for small passerines due to their high mass-specific metabolic rates. Basal metabolic rate (BMR) reflects the energy expended by endothermic animals for basic physiological processes and constitutes a major part of their daily energy budget. Some birds have been shown to employ compensatory mechanisms during food shortages, temporarily reducing these self-maintenance expenditures without using hypothermia. However, the mechanisms of BMR adjustment remain unexplored. In the present study, we assessed the phenotypic variation in basal thermogenesis of Eurasian Tree Sparrows (Passer montanus) by comparing a control group to groups fasted for 6, 12, 18, and 24 h. We focused on the correlation between a reduction in energy metabolism and the alterations of cellular metabolic activities, mitochondrial substrate supply, and changes in serum thyroid hormones during fasting. Our data indicated that fasting groups had significantly lower body mass, BMR, body temperature, and body fat content. Furthermore, fasting groups had significantly lower glycogen levels, mitochondrial state 4 respiration and cytochrome c oxidase (CCO) activity in the liver, and CCO activity in pectoral muscle. The levels of avian uncoupling protein (av-UCP) mRNA were significantly reduced, while the levels of myostatin protein in pectoral muscle were significantly increased in the fasting groups. Furthermore, the groups subjected to fasting exhibited significantly lower levels of serum glucose, triglyceride, thyroxine (T4), and triiodothyronine (T3). Positive correlations were observed between the following pairs of variables: log BMR and log body mass, log body mass and log body fat, log BMR and log state 4 respiration in the liver, log BMR and log CCO activity in the liver and muscle, log BMR and log av-UCP mRNA expression, whereas a negative correlation was observed between log BMR and log myostatin level. In addition, a positive correlation was also detected between log T3 and each of the following: log BMR, state 4 respiration, and log CCO activity in the liver. Our results suggested that decreased metabolic thermogenesis via down-regulation in cellular aerobic capacity of organs and serum thyroid hormones may be an important survival strategy for fasting Tree Sparrows to reduce energy expenditure.